THE ALGORITHM DESIGN AND DRIVING FORCE SYSTEM IN THEMATIC ROBOT OF PADDY FARMING - Syaiful Amri; Ade Reza Septiadi (Merdeka Malang University, 2020)
Indonesia Thematic Robot Contest (Kontes Robot Tematik Indonesia (KRTMI)) is one of division in Indonesia Robot Contest (Kontes Robot Indonesia (KRI)) which tailor to the nation necessity that is demanding to be resolved. In this KRTMI division robot contest, the robot, that was able to be controlled by a remote wirelessly, was designed in order to perform paddy planting simulation, pluck grasses among paddies, and harvest paddy. In this robot contest, the robot was also designed to be able to pass through mushy soil while planting paddy and plucking grasses. From the robot concept that is based on the rules, the robot used primary driving force with two DC gearbox motor which was paired with rubber track type wheels to be able to pass through mushy soil. While for performing paddy planting and grass plucking, a combination of DC gearbox motor and pneumatic was applied. The entire operation of the robot was controlled with wireless joystick command by a robot operator. The result of this research could be tested for its motor driver response efficiency and relay on-off control for the pneumatic which was controlled wirelessly through a joystick. The testing results were efficiency of 99% and control response success of 100%.